2021
DOI: 10.1159/000515755
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Repeated Intravitreal Applications of Atropine on Choroidal Thickness in Alert Chickens

Abstract: <b><i>Introduction:</i></b> Atropine, a muscarinic antagonist, is known since the 19th century to inhibit myopia development in children. One of its effects is that it stimulates choroidal thickening. Thicker choroids, in turn, have been linked to myopia inhibition. We used the atropine-stimulated choroidal response in the chicken to learn more about the time courses and amplitudes of the effects of atropine, as well as whether repeated applications lead to accumulation or desensitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
(74 reference statements)
4
9
0
Order By: Relevance
“…All injections were performed under mild ether anesthesia. The intravitreal injection procedure in the chicken is well established (e.g., [11,[24][25][26]) and, as in previous studies, we never observed ocular inflammations.…”
Section: Intravitreal Injectionssupporting
confidence: 87%
See 2 more Smart Citations
“…All injections were performed under mild ether anesthesia. The intravitreal injection procedure in the chicken is well established (e.g., [11,[24][25][26]) and, as in previous studies, we never observed ocular inflammations.…”
Section: Intravitreal Injectionssupporting
confidence: 87%
“…We had previously found that intravitreal atropine causes prominent, but transient, choroidal thickening in the chicken eye. The effect was also observed in the contralateral eye where it was more transient [11]. Time courses and magnitudes of choroidal thickness changes in atropine-injected eyes and their saline-injected fellow eyes closely matched observations from our previous study [11].…”
Section: Experiments 1-effects Of a Dopamine Antagonist On Atropine-i...supporting
confidence: 85%
See 1 more Smart Citation
“…These findings suggest that the improved effect of 0.01% atropine eye drop instillation on SE might be affected by the shortened AL. Recently, it has been reported that one of the effects of atropine is that it stimulates choroidal thickening ( Chiang et al, 2020 ; Mathis et al, 2021 ; Ye et al, 2021 ). However, our findings were specifically created to have opposing effects at 6 months after atropine eye drop instillation.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis can probably be best supported by long-term studies in children, 21 , 22 although it may be difficult to finally determine what is cause or consequence. 13 , 23 25 …”
Section: Introductionmentioning
confidence: 99%